Binge Alcohol Exposure in Adolescence Impairs Normal Heart Growth. Issue 9 (5th May 2020) - Ai, Lizhuo; Perez, Edith; Asimes, AnnaDorothea; Kampaengsri, Theerachat; Heroux, Maxime; Zlobin, Andrei; Hiske, Mark A.; Chung, Charles S.; Pak, Toni R.; Kirk, Jonathan A.
Abstract : Background: Approximately 1 in 6 adolescents report regular binge alcohol consumption, and we hypothesize it affects heart growth during this period. Methods and Results: Adolescent, genetically diverse, male Wistar rats were gavaged with water or ethanol once per day for 6 days. In vivo structure and function were assessed before and after exposure. Binge alcohol exposure in adolescence significantly impaired normal cardiac growth but did not affect whole‐body growth during adolescence, therefore this pathology was specific to the heart. Binge rats also exhibited signs of accelerated pathological growth (concentric cellular hypertrophy and thickening of the myocardial wall), suggesting a global reorientation from physiologic to pathologic growth. Binge rats compensated for their smaller filling volumes by increasing systolic function and sympathetic stimulation. Consequently, binge alcohol exposure increased PKA (protein kinase A) phosphorylation of troponin I, inducing myofilament calcium desensitization. Binge alcohol also impaired in vivo relaxation and increased titin‐based cellular stiffness due to titin phosphorylation by PKCα (protein kinase C α). Mechanistically, alcohol inhibited extracellular signal‐related kinase activity, a nodal signaling kinase activating physiology hypertrophy. Thus, binge alcohol exposure depressed genes involved in growth. These cardiac structural alterations from binge alcohol exposure persisted through adolescence even after cessation of ethanol exposure. Conclusions: Alcohol negatively impacts function in the adult heart, but the adolescent heart is substantially more sensitive to its effects. This difference is likely because adolescent binge alcohol impedes the normal rapid physiological growth and reorients it towards pathological hypertrophy. Many adolescents regularly binge alcohol, and here we report a novel pathological consequence as well as mechanisms involved.